The Contexts of Diaspora Citizenship Somali Communities in Finland and the United States - Armila, Päivi; Kananen, Marko; Kontkanen, Yasemin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores the social participation, identification and transnational practices of Somalis living in Finland and the United States. Through a multifaceted collection of chapters which are based on data ranging from legislation and policy documents to welfare indicators and interviews, this book explores how Somali migrants experience and explore their identities and belongings, and how they strive for participation as (diaspora) citizens of their sending and receiving societies. The case studies are conducted in two countries that differ greatly in terms of their social system, migration history and integration policies and as such they provide an opportunity to explore how different social, political and legal orders influence the life-courses and wellbeing of migrant populations. Furthermore, the book highlights how the fate of the Somalis as a global diaspora is routinely intertwined with the changes in the global political climate and the state-level political processes reflecting it. This book will be of great interest to researchers, students and lecturers of migration and diaspora, as well as individuals working with (Somali) migrants.
PROLOGUE -- Part I: INTRODUCTION: ABOUT THIS COLLECTION -- Part II: PERSPECTIVES TO DIASPORA CITIZENSHIPS: CONTEXTS 1. Facts and Figures: Somalis in Finland and in the United States Marko Kananen & Ville-Samuli Haverinen 2. The Newest African-Americans?:Somali Struggles for Belonging Cawo M. Abdi 3.Mainstream or Margins? How Somalis Perceive Their Status and Possibilities in Finnish and American Societies? Marko Kananen 4. The Call of the Homeland: "My Relationship to Somalia is Difficult to Explain" Marko Kananen -- Part III: ACTING AS DIASPORA CITIZENS: AGENCIES 5. Subject, Object, Predicate? Somali Migrants' Subject Positions in a Local Finnish Integration Scene Päivi Armila & Yasemin Kontkanen 6. Somalis In America's Heartland: Columbus,Ohio Stefanie Chambers 7. Integration, Finnish Somalis and Their Right to Everyday Life Tiina Sotkasiira 8. Somali Diaspora Women and Sense of Identity and Belonging Habon Abdulle 9.Diaspora Citizenship: Silenced, Stigmatized, Outlying - and Campaigning Päivi Armila & Yasemin Kontkanen Part IV: STUDYING DIASPORA CITIZENSHIP: THEORETICAL AND METHODOLOGICAL NOTIONS 10. Of Premises for Cross-National Comparisons 11. Notions about Cross-National Comparative Social Sciences and the Societal Role of Researchers Ville-Samuli Haverinen -- EPILOGUE -- ABOUT THE AUTHORS. .
Keywords: Emigration and immigration; Political sociology; Human Migration; Political Sociology